DESKRIPSI KEMAMPUAN GURU DALAM MERANCANG PENILAIAN AUTENTIK DALAM PEMBELAJARAN AKTIF - Iis Puspa Subekti; Hairida; Masriani; Rahmat Rasmawan; Rody Putra Sartika (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
This article describes the implementation of teachers’ competence in designing authentic assessments for active learning and identifies the inhibiting factors that affect teachers in designing these assessments for natural science learning subjects. The research employed a descriptive method with science teachers at SMPN 2 Pontianak as the subjects. Data were collected through interviews and questionnaires, and lesson plans designed by the teachers were analyzed. The interview guides and lesson plan review instruments were validated beforehand using the Gregory test. The results indicate that science teachers’ competence in designing authentic assessments was still inadequate across cognitive, affective, and psychomotor domains. This was primarily due to the misalignment of basic competencies with assessment indicators and the fact that most teachers did not design assessment rubrics. Additional obstacles included managing simultaneous assessment activities with large class sizes, limiting teachers’ ability to fully implement authentic assessments. Therefore, teachers are encouraged to enhance their skills in designing assessment instruments, implementing authentic assessments, and managing learning time effectively.